2021
DOI: 10.1002/phar.2513
|View full text |Cite
|
Sign up to set email alerts
|

Use of psychiatric medication by college students: A decade of data

Abstract: Objectives: Given the rising prevalence of psychiatric symptomatology among college students, this analysis aims to identify temporal trends in psychiatric medication usage.Methods: This analysis used data from the Healthy Minds Study Survey administered between 2007 and 2019, yielding a sample of 320,817 university students. Survey data were examined via descriptive analyses.Results: Over the last decade from 2007 to 2018-2019, there was an increase in use of nearly all classes of psychiatric medications, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 12 publications
(30 reference statements)
2
16
0
Order By: Relevance
“…Mental health care needs of college students have been a growing concern due to the rising prevalence of these illnesses on college campuses. 20,21 The 2019 American College Health Association survey found that anxiety and depression are two of the most frequent health problems college students face during the academic year. 22 Furthermore, among students with at least one mental health problem, 60% had at least one mental health problem that persisted 2 years later.…”
Section: Mental Healthmentioning
confidence: 99%
See 4 more Smart Citations
“…Mental health care needs of college students have been a growing concern due to the rising prevalence of these illnesses on college campuses. 20,21 The 2019 American College Health Association survey found that anxiety and depression are two of the most frequent health problems college students face during the academic year. 22 Furthermore, among students with at least one mental health problem, 60% had at least one mental health problem that persisted 2 years later.…”
Section: Mental Healthmentioning
confidence: 99%
“…20,21 The 2019 American College Health Association survey found that anxiety and depression are two of the most frequent health problems college students face during the academic year. 22 Furthermore, among students with at least one mental health problem, 60% had at least one mental health problem that persisted 2 years later. 23 As the prevalence of mental health disorders has grown, more students are receiving medication for these illnesses.…”
Section: Mental Healthmentioning
confidence: 99%
See 3 more Smart Citations